Bone-targeting polymer vesicles for simultaneous imaging and effective malignant bone tumor treatment. (February 2021) - Zhou, Xue; Yan, Ning; Cornel, Erik J.; Cai, Haidong; Xue, Shaobo; Xi, Hao; Fan, Zhen; He, Shisheng; Du, Jianzhong
Abstract: We present a bone-targeting polymer vesicle with excellent single photon emission computed tomography/computed tomography (SPECT/CT) imaging capability and high antitumor drug delivery efficiency as an integrated platform for the simultaneous diagnosing and treatment of malignant bone tumors. This polymer vesicle can be self-assembled from poly( ε -caprolactone)67 - b -poly[( L -glutamic acid)6 - stat -( L -glutamic acid-alendronic acid)16 ] (PCL67 - b -P[Glu6 - stat -(Glu-ADA)16 ]), directly in water without the aid of a cosolvent. SPECT/CT dynamically tracked the drug distribution in the bone tumor rabbit models, and the tumor size was significantly reduced from >2.0 cm 3 to <0.6 cm 3 over 11 days. The pathological analysis demonstrated obvious necrosis and apoptosis of the tumor cells. Overall, this bone-targeting polymer vesicle provides us with a new platform for the combination of real-time diagnosis and therapy of malignant bone tumors. Graphical abstract: Image 1